Multimodal nonlinear microscopic investigations on head and neck squamous cell carcinoma: Toward intraoperative imaging. Issue 9 (18th September 2012) - Meyer, Tobias; Guntinas‐Lichius, Orlando; von Eggeling, Ferdinand; Ernst, Günther; Akimov, Denis; Schmitt, Michael; Dietzek, Benjamin; Popp, Jürgen; Chen, Amy
Abstract Background Prognosis and appropriate treatment of head and neck squamous cell carcinoma (HNSCC) depend on the tumor type routinely derived by invasive histopathology. A promising noninvasive alternative is nonlinear optical imaging, which is capable of in vivo tissue visualization for tumor typing and grading. Methods and Results Thin tissue sections from 3 patients aged 56 to 60 years presenting advanced carcinoma of the hypopharynx, larynx, and left tonsil were investigated by coherent anti‐Stokes Raman scattering (CARS), second‐harmonic generation (SHG), and 2 photon excited fluorescence (TPEF) to study the morphochemistry of the tissues. Morphologic alterations of prognostic significance, such as cell density, nuclear to cytoplasm ratio, and keratinization as well as the underlying compositional changes during malignant transformation were determined, such as the distributions of lipids, collagen, and autofluorophors. Conclusions Nonlinear imaging provides a noninvasive optical biopsy of the epithelial layer comparable to staining microscopy. By integration into an operational microscope, routine screening of suspicious lesions and surgical guidance can be realized. © 2012 Wiley Periodicals, Inc. Head Neck, 2013